Recurrent ventricular tachycardia after cardiac sympathetic denervation: Prolonged cycle length with improved hemodynamic tolerance and ablation outcomes. (30th June 2020) - Hayase, Justin; Dusi, Veronica; Do, Duc; Ajijola, Olujimi A.; Vaseghi, Marmar; Lee, Jay M.; Yanagawa, Jane; Hoftman, Nir; Revels, Sha'Shonda; Buch, Eric F.; Khakpour, Houman; Fujimura, Osamu; et al.
Abstract: Introduction: Cardiac sympathetic denervation (CSD) is utilized for the management of ventricular tachycardia (VT) in structural heart disease when refractory to radiofrequency ablation (RFA) or when patient/VT characteristics are not conducive to RFA. Methods: We studied consecutive patients who underwent CSD at our institution from 2009 to 2018 with VT requiring repeat RFA post‐CSD. Patient demographics, VT/procedural characteristics, and outcomes were assessed. Results: Ninety‐six patients had CSD, 16 patients underwent RFA for VT post‐CSD. There were 15 male and 1 female patients with mean age of 54.2 ± 13.2 years. Fourteen patients had nonischemic cardiomyopathy. A mean of 2.0 ± 0.8 RFAs for VT was unsuccessful before the patient undergoing CSD. The median time between CSD and RFA was 104 days (interquartile range [IQR] = 15–241). The clinical VT cycle length was significantly increased after CSD both spontaneously on ECG and/or ICD interrogation (355 ± 73 ms pre‐CSD vs. 422 ± 94 ms post‐CSD, p  = .001) and intraprocedurally (406 ± 86 ms pre‐CSD vs. 457 ± 88 ms post‐CSD, p  = .03). Two patients had polymorphic and 14 had monomorphic VT (MMVT) pre‐CSD, and all patients had MMVT post‐CSD. The proportion of mappable, hemodynamically stable VTs increased from 35% during pre‐CSD RFA to 58% during post‐CSD RFA ( p  = .038). At median follow‐up of 413 days (IQR = 43–1840) after RFA, eight patients had no further VT. Conclusion: RFA for recurrent MMVT post‐CSD is a reasonable treatment option with intermediate‐term clinical success in 50% of patients. Clinical VT cycle length was significantly increased after CSD with associated improvement in mappable, hemodynamically tolerated VT during RFA.